Monitoring Ionosphere over South America: the MImOSA and MImOSA2 projects - Cesaroni, Claudio; Alfonsi, Lucilla; Veettil, Sreeja Vaddake; Park, Jihye; Romero, Rodrigo; Linty, Nicola; Dovis, Fabio; Barroca, Daniele [UNESP]; Ortega, Mayara Cobacho [UNESP]; Perez, Raul Orus; IEEE (Ieee, 2015)
MImOSA and MImOSA2 are two projects funded in the framework of the ALCANTARA Initiative of the European Space Agency. MImOSA (Monitoring the Ionosphere Over South America) was a competence survey aimed at assessing the capabilities of the South American (SA) countries to monitor and investigate the ionosphere. This was done to understand how the currently existing facilities could be integrated with new GNSS-based installations to effectively support space weather activities in SA. The experience and the heritage acquired through MImOSA have led to a new project, MImOSA2 (Monitoring Ionosphere Over South America to support high precision applications), focused on technological applications and aimed at exploiting the data from selected facilities to support high-precision GNSS based services in SA. MImOSA2 is dedicated to the analysis, through an original method, of GNSS data acquired by a dense network of 50 Hz receivers to demonstrate the improvements on positioning accuracy when GNSS signal degradation due to harsh ionospheric conditions is taken into account. The multi-constellation capability of the adopted instrumentation allows generating ionospheric maps with a very fine spatial and temporal resolution to take into account the effects caused by the electron density irregularities. The synergy between European institutions and the Brazilian partner, and the use of newly dedicated algorithms offer the opportunity to demonstrate the improvements of positioning capability on long baseline RTK (Real Time Kinematic) and NRTK (Network RTK) (VRS approach) solutions in the considered region. Moreover, the effects of anthropogenic interference on GNSS L-band signals recorded in Presidente Prudente is under investigation, to evaluate the effects of environmental disturbances on GNSS derived measurements, by means of configurable communication devices and a software defined radio receiver.
Keywords: low latitude ionosphere; TEC; scintillation; VRS; PPP; RTK; GNSS interference; SDR